THE POTENTIAL OF BLACK CUMIN SEED OIL (Nigella sativa L.) AS A HALAL ANTIBACTERIAL AGENT AGAINST EXTENDED SPECTRUM ?-LACTAMASE (ESBL)-PRODUCING ESCHERICHIA COLI - Tomi; Nurrosyidah, Iif Hanifa; Muzzayinah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Infectious diseases remain a major issue in tropical countries such as Indonesia. Infectious diseases can be caused by pathogenic microorganisms such as bacteria, viruses, parasites, or fungi. Development of antibacterial agents from natural sources is essential to combat the growing issue of antibiotic resistance. One potential plant is black cumin seed (Nigella sativa L.) contains thymoquinone, a compound known for its antibacterial properties. In addition to thymoquinone, the essential oil of black cumin contains thymol, carvacrol, and p-cymene, along with metabolites such as alkaloids, saponins, and tannins. This study aimed to investigate the antibacterial activity of black cumin seed oil (Nigella sativa L.) against Extended Spectrum ?-lactamase-producing Escherichia coli (E. coli ESBL). The antibacterial test in this study used the disc diffusion method at various concentrations, including 100%, 75%, 50%, and 25%. The extract was obtained by distillation, using pure water as the solvent. The test groups included a negative control, positive control using chloramphenicol, and negative control using pure water. The results of the antibacterial activity test showed that the positive control produced an average inhibition zone of 25 mm, classified as susceptible, whereas the negative control showed no inhibition zone (0 mm). At 100% concentration, the inhibition zone averaged 18,67 mm, at 75% it averaged 16 mm, at 50% it averaged 11,67 mm, and at 25%, the inhibition zone averaged 6,67 mm. The three lower concentrations were categorized as resistant.